Epigenetic aging in adult neurogenesis. Issue 4 (9th January 2023) - Zocher, Sara; Toda, Tomohisa
Abstract: Neural stem cells (NSCs) in the hippocampus generate new neurons throughout life, which functionally contribute to cognitive flexibility and mood regulation. Yet adult hippocampal neurogenesis substantially declines with age and age‐related impairments in NSC activity underlie this reduction. Particularly, increased NSC quiescence and consequently reduced NSC proliferation are considered to be major drivers of the low neurogenesis levels in the aged brain. Epigenetic regulators control the gene expression programs underlying NSC quiescence, proliferation and differentiation and are hence critical to the regulation of adult neurogenesis. Epigenetic alterations have also emerged as central hallmarks of aging, and recent studies suggest the deterioration of the NSC‐specific epigenetic landscape as a driver of the age‐dependent decline in adult neurogenesis. In this review, we summarize the recently accumulating evidence for a role of epigenetic dysregulation in NSC aging and propose perspectives for future research directions.